2023
DOI: 10.3389/fphys.2023.1118653
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect cardiovascular and cardiometabolic sequelae of the combined anti-retroviral therapy on people living with HIV

Abstract: With reports of its emergence as far back as the early 1900s, human immunodeficiency virus (HIV) has become one of the deadliest and most difficult viruses to treat in the era of modern medicine. Although not always effective, HIV treatment has evolved and improved substantially over the past few decades. Despite the major advancements in the efficacy of HIV therapy, there are mounting concerns about the physiological, cardiovascular, and neurological sequelae of current treatments. The objective of this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Further, the availability of objective HIV-specific factors (i.e., viral load and CD4 + cell count) would have provided clarity as to the impact of HIV-specific factors on ASCVD risk, and if these vary by sex [18,21]. Additionally, although it is now well documented than INSTIs are associated with better cardiovascular risk profiles compared to other classes of ART, INSTIs were not the preferred line of drug during the entire time 2011–2019 time period, which limits our ability to detect sex-based differences in ASCVD risk associated with drug class [30–32]. Although we were able to examine the relationships between age and ASCVD risk among WLHIV, we did not have data on menopausal status, which would have provided further insight into the mechanisms influencing sex-specific ASCVD risk among PWH [18,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the availability of objective HIV-specific factors (i.e., viral load and CD4 + cell count) would have provided clarity as to the impact of HIV-specific factors on ASCVD risk, and if these vary by sex [18,21]. Additionally, although it is now well documented than INSTIs are associated with better cardiovascular risk profiles compared to other classes of ART, INSTIs were not the preferred line of drug during the entire time 2011–2019 time period, which limits our ability to detect sex-based differences in ASCVD risk associated with drug class [30–32]. Although we were able to examine the relationships between age and ASCVD risk among WLHIV, we did not have data on menopausal status, which would have provided further insight into the mechanisms influencing sex-specific ASCVD risk among PWH [18,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In the PI group, however, only 13 (22%) of 59 patients were treated with ATV (8 ATV/r and 5 unboosted ATV); moreover, we was not able to identify the impact of the different PIs on the development of cardiovascular diseases. However, the intent of the study is to evaluate the cardiovascular risk related altogether to the class of PIs, which was also highlighted in a recent review of Batta et al [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Altered clot structure is a known contributing factor in thrombotic-related cardiovascular complications [ 19 ], as clots with tightly packed, dense fibrin networks tend to be more resistant to lysis and contributing to thromboembolic events [ 19 , 20 ]. This may result in adverse complications such as stroke and myocardial infarction, which are also evident in PLWH [ 12 , 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The global community persists in employing strategies to improve ART, expand its coverage and enhance compliance among users with a view to improving health and reducing new infection rates [8,9]. However, evidence has emerged that demonstrates cardiovascular disease (CVD) to be a growing concern and a leading cause of morbidity and mortality among PLWH on ART [10][11][12]. It is reported that ART use is associated with increased inflammation, dyslipidaemias, endothelial lining injuries as well as altered coagulation [13][14][15].…”
Section: Introductionmentioning
confidence: 99%